Kajian Kinerja Penatua Pemuda Dalam Membangun Kesadaran Pemuda Untuk Beribadah Di Jemaat GMIM Efarata Wusa Wilayah Mapanget IV - Wagania, Stevanoch M. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
Worship is something that is very important for Christians, especially among today's young people. This article aims to discuss the performance or role of Youth Elders in building youth awareness in worshiping in the